Exploring the Collaboration Skills among Architecture Students: A Quantitative Study in North Cyprus - Karimi, Hirou; Farivarsadri, Guita (Mdpi, 2024)
This research investigates the collaboration competencies among architecture students at Eastern Mediterranean University, in North Cyprus, highlighting the necessity for curricular enhancements to foster teamwork skills essential for professional practice. A structured questionnaire was administered to 77 final-year students, evaluating their knowledge, abilities, and experiences in collaborative settings. Factor analysis revealed twelve key components of collaboration, indicating moderate skill levels overall. Notably, students excelled in work quality, self-reflection, and time management yet exhibited deficiencies in team learning, role adaptability, and equitable idea contribution. This study identified five critical dimensions of teamwork: interpersonal facilitation, collaborative leadership, engagement contribution, active listening, and transparent information exchange. A strong correlation emerged between students' perceived readiness for collaborative work and their self-rated leadership and interpersonal skills. Comparative analysis showed distinct collaboration skill sets between international and domestic students and across different academic years. These insights emphasize the imperative for architectural education to progressively incorporate specific learning activities and interventions to cultivate teamwork competencies systematically. The development of such skills is vital for preparing graduates to effectively navigate and lead within the multidisciplinary contexts they will face. Recommendations include curriculum redesign to integrate explicit teamwork instruction, faculty development programs, and fostering an educational culture that consistently values collaboration. Future studies should investigate effective pedagogical strategies for nurturing collaboration skills and examine how individual variances affect the acquisition of these critical abilities.
Keywords: collaboration abilities; architecture students; self-assessed skills; learning trajectories; collaborative leadership